Analisis Penggunaan Bahasa Indonesia pada Promosi Wisata dalam Media Sosial Instagram Akun @Dagowisatatours - Azizah Febi Rahmawati; Zahra Mahsa Lestari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Promotional media for tourism advertising, Indonesian is used as a communication tool to convey ideas in selling a product or offering services. This research aims to analyze the use of Indonesian in tourism promotion on the social media account @dagowisatatours. To promote tourism services and tourist locations, the @dagowisatatours account uses Instagram social media to expand market reach and disseminate information more quickly. The research in this article identifies the dynamics of the use of Indonesian which is often used in tourism promotional media, analyzes the effectiveness of the use of promotional language in promotional media in increasing sales in promotional media. The research results show that the use of Indonesian in promoting tourism services and tourism destinations on the @dagowisatatours account is presented with interesting word choices and methods via the Instagram social media platform.